Preparasi dan Karakterisasi Karbon Aktif dari Kulit Kacang Tanah (Arachis Hypogaea L.) - Yolla Rama Wanda; Ananda Putra (Departemen Kimia FMIPA UNP, 2021)
Organic waste was a problem for society and government. Because that was due of environmental pollution. Organic waste was divided into organic waste which was easily broken down because has relatively short chemical chain and organic waste that does not decompose easily because has a relatively long chemical chain. One of the efforts that might be a solution for processing this waste by using into it activated carbon. The purposes of that experiment were to prepare and characterize activated carbon from peanut shell (Arachis Hypogaea L.). Carbon from peanut shell was prepared by pyrolysis at 300˚C, 350˚C and 400˚C for 1 hour. After pyrolysis, the carbon from the peanut shell was mashed and filtered using 150 μm sieve. And then, tested the moisture content, ash content, vapor content, and bound carbon content. The resulted showed the highest bound carbon content pyrolysis at 350˚C. The carbon was activated by chemical activation, with various of compounds and different concentrations. The resulted showed the highest bounded carbon content was found 64,7%. The best Activation reagent was ZnCl2 of 6N and made improved bounded carbon content was 85,78%. The water content was found 1,1%, the ash content was found 1,34%, and the vapor content was 12,88%. Based on the resulted activated carbon from peanut shell comformed the SNI 06-3730-1995.